A technique based on the quasi-actual feed for suppressing sidelobe levels of reflector antenna. Issue 5 (3rd July 2020) - Yu, Xinhua; Wang, Jun; Huang, Xingqiang; Fu, Wenjie; Sun, Guiyu; Niu, Xinjian; Li, Simin; Jiang, Yannan; Wang, Xin; Wang, Yiying
ABSTRACT: A sidelobe-suppression technique for the reflector antenna is proposed. Compared to the conventional reflector antenna analysis technique, the proposed technique adopts the novel quasi-actual feed instead of the traditional imaginary feed to calculate and optimize the radiation pattern of the reflector antenna. The calculated and the optimized radiation results obtained by the proposed technique are more accurate since the quasi-actual feed data is closer to that of the practical feed. In the proposed technique, the sidelobes are suppressed by optimizing the shape of the reflector illuminated by the quasi-actual feed. The reflector shape is smoothly transformed by the non-uniform rational B-spline technique and the scatter of the reflector is efficiently calculated by the physical optics and the Gauss-Legendre quadrature algorithms. The pattern result of this proposed technique is compared with the result simulated by FEKO software, a good agreement is achieved and has a higher efficiency. As an example of applying the proposed technique, an unshaped and a shaped reflector antennas with the same feed and the same size are designed, fabricated and tested, and the measured results agree well with the expectations on the low sidelobe characteristic.